Model of Local Original Revenue Enhancement Based on Management Capacity: A Quantitative Study of Local Revenue Growth in Southwest Papua - Naa, Ernawati Miyane; Yunus, Muhammad; Ibrahim, Muhammad Akmal; Dwijayanti, Avrina (KnE Social Sciences, 2025)
This study aims to analyze the effect of management capacity on increasing local revenue (PAD) in West Papua Province, focusing on six main dimensions: strategic planning, resource organization, effective leadership, program implementation, performance control, and change management. The study uses a quantitative approach with an explanatory design on 50 respondents selected through purposive sampling techniques from employees at the West Papua Provincial Revenue Agency. Data were collected through a questionnaire with a Likert scale of 1-5 that had been tested for validity and reliability. Data analysis used multiple linear regression and path analysis to test partial and simultaneous effects and identify direct and indirect effects between variables. The results show that all research hypotheses (H₁-H₇) were accepted, with management capacity proven to have a very strong influence on increasing PAD (R² = 0.966). Effective leadership (β = 0.412) and change management (β = 0.398) were the most dominant factors in the increase. Path analysis confirmed that effective leadership had the highest total influence (0.491), with direct and indirect effects through mediating variables. This finding has implications for the need to develop leadership and change management capacity as a priority in efforts to optimize PAD in new autonomous regions.